Ontogenetic shift and feeding habits of the European hake (Merluccius merluccius L., 1758) in Central and Southern Tyrrhenian Sea (Western Mediterranean Sea): A comparison between past and present data. Issue 3 (23rd March 2022) - D'Iglio, Claudio; Porcino, Nunziatina; Savoca, Serena; Profeta, Adriana; Perdichizzi, Anna; Armeli Minicante, Enrico; Salvati, Davide; Soraci, Francesco; Rinelli, Paola; Giordano, Daniela
Abstract: The present paper aims to investigate the ecological role of Merluccius merluccius, Linnaeus, 1758, in southern and central Tyrrhenian Sea (GSA 10, Resolution GFCM/33/2009/2 General Fisheries Commission for the Mediterranean), analyzing ontogenetic diet shifts, geographical variations on prey composition, and feeding habits. A total of 734 hake specimens ranging in size between 6 cm and 73 cm (Total Length, TL) were collected in 2018. In order to evaluate ontogenetic shifts in prey composition, samples were divided into five size classes and for each class the quantitative feeding indices have been calculated. The statistical analysis, based on index of relative importance percentage (%IRI), resulted in three trophic groups. The most abundant prey found in the immature hake specimens (size class I) were the Euphausiids, Stylocheiron longicorne and Mysidacea, while for samples with a total length over 10.5 cm were crustaceans and fish. Engraulis encrasicolus was the most abundant fish prey identified, followed by Boops boops and Myctophids. The high presence of Euphausiids, Mysids, Myctophidae, and Sternoptychidae in classes I, II, II, and IV (6–23 cm) showed the relevant role of mesopelagic fauna in hake diets, with an essential organic matter and energy flow from the mesopelagic to the epipelagic environment. Additionally, decapod crustaceans were found in the stomach contents of hakes belonging to class V (with size over 36 cm TL), which is notable considering that our study area includes an important decapod crustacean fishing area. Abstract : This study investigates the feeding habits of European hake in the southern Tyrrhenian Sea. It is a clear example of inverse energy flow between mesopelagic and epipelagic biocenosis. The high occurrence of Euphausiids, Myctophids, and Sternoptychids found in gut contents of juvenile hake showed the importance of energy and organic matter from deeper strata for the growth of young hakes.